Design and manufacture of a ten ton capacity wedge jack - Azim, M. Anwarul; Amin, A. K. M. Nurul; Khan, Ahsan Ali (1989)
A Wedge Jack of relatively small dimensions (300 x 100 x 50 mm), but extremely high load carrying capacity (10 tons) has been designed for precision lifting of turbine shaft and its bearing cases for their proper alignment at Ghorasal Power Plant. The work was unique of its kind in Bangladesh, since it was the first venture of installation of a new power plant using local technology and expertise. The Jack was a key inventory item, without which the erection work was not technologically feasible. Its import from abroad or local manufacture using foreign expertise would involve huge cost and delay in the erection. Design of the same by an expert team of B.U.E.T. has solved the above mentioned problem. The designed Wedge Jack consists of an upper plate, a lower plate, two wedges and threaded shaft. Rotation of the shaft in one direction facilitates lifting up of the upper plate along with the given load, while rotation in the opposite direction lowering down of the same. Safety factors in the range from 1.5 to 3.5 for various parts of the Jack have been ensured by the design. For ease of production a few sample pieces of the same were manufactured under the supervision of the designers. The manufactured Wedge Jacks were tested for accuracy and the required load carrying capacity.